Determinants of Niger Seed Commercialization in the Jabitehenan District, West Gojjam Zone, Amhara National Regional State, Ethiopia - Mulat Mengstu; Chernet Worku; Sosina Bezie (AGRARIS: Journal of Agribusiness and Rural Development Research, 2023)
Ethiopia’s oil seed industry is expanding swiftly to meet rising domestic and foreign demand, assisting the country in generating foreign exchange earnings and income. This study aimed to quantify the level of household commercialization of Niger seed output and analyze the determinants affecting it. This research utilized a three-stage random sampling technique to gather quantitative and qualitative data from primary and secondary sources. The primary data came from sampled households through a semi-structured interview. Moreover, 150 samples were selected randomly. Descriptive statistics and the Tobit censored regression model were utilized to analyze the data. SPSS version 20 and STATA 13 software were also employed. The average level of Niger seed commercialization in the area was 0.71%. Several determinants, including the amount of Niger seed output, market information, frequency of extension service, training access, age, and total livestock unit, influenced the level Niger seed. The regional government and district leaders should strengthen the provision of different training to raise the production, productivity, and level of Niger seed commercialization by enhancing the marketable surplus of Niger seeds.